A High-Caliber View of the Bullet Cluster through JWST Strong and Weak Lensing Analyses - Sangjun Cha; Boseong Young Cho; Hyungjin Joo; Wonki Lee; Kim HyeongHan; Zachary P. Scofield; Kyle Finner; M. James Jee (The Astrophysical Journal Letters)
The Bullet Cluster (1E 0657-56) is a key astrophysical laboratory for studying dark matter, galaxy cluster mergers, and shock propagation in extreme environments. Using new JWST imaging, we present the highest-resolution mass reconstruction to date, combining 146 strong lensing constraints from 37 systems with high-density (398 sources arcmin ^−2 ) weak lensing data, without assuming that light traces mass. The main cluster’s mass distribution is highly elongated (northwest–southeast) and consists of at least three subclumps aligned with the brightest cluster galaxies. The subcluster is more compact but elongated along the east–west direction, with a single dominant peak. We also detect a possible mass and intracluster light (ICL) trail extending from the subcluster’s eastern side toward the main cluster. Notably, these detailed features are closely traced by the ICL, with a modified Hausdorff distance of 19.80 ± 12.46 kpc. Together with multiwavelength data, the complex mass distribution suggests that the merger history of the Bullet Cluster may be more complex than previous binary cluster merger scenarios.